2008
DOI: 10.1002/cyto.b.20452
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of multiplex suspension array large‐panel kits for profiling cytokines and chemokines in rheumatoid arthritis patients

Abstract: Background Multiplex analysis allows measurements of a large number of analytes simultaneously in each sample. Based on the Luminex multiplex technology (xMAP), kits for measuring multiple cytokines and chemokines (immunomodulators) are commercially available and are useful in investigations on inflammatory diseases. This study evaluated four multiplex kits (Bio-Plex, LINCOplex, Fluorokine, and Beadlyte) that contained 27, 29, 20 and 22 analytes each, respectively, for the analysis of immunomodulators in plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…Poulin et al (14) found that IL-9 mRNA and protein were highly expressed in a mouse model of fully mismatched heart transplantation. A previous study also demonstrated that serum levels of IL-9 and additional pathologic cytokines were elevated after the second immunization of rheumatoid arthritis (RA) (15), while Khan et al (16) further confirmed that IL-9 and some another inflammatory cytokines were descended following treatment with rituximab, indicating that IL-9 plays a pro-inflammatory role in RA. Additional evidence indicates that IL-9 cytokine may contribute to the development of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 84%
“…Poulin et al (14) found that IL-9 mRNA and protein were highly expressed in a mouse model of fully mismatched heart transplantation. A previous study also demonstrated that serum levels of IL-9 and additional pathologic cytokines were elevated after the second immunization of rheumatoid arthritis (RA) (15), while Khan et al (16) further confirmed that IL-9 and some another inflammatory cytokines were descended following treatment with rituximab, indicating that IL-9 plays a pro-inflammatory role in RA. Additional evidence indicates that IL-9 cytokine may contribute to the development of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 84%
“…A linear model fit was determined for each analyte by using the LIMMA package in R. The data corresponding to immunomodulators (and antibodies) with a positive signal were combined in a two-step process to obtain an initial analytical data set. Relative fold changes (increase or decrease) of the levels of both immunomodulators and antibodies between the healthy controls and patient groups in the pilot as well as the expanded experiments were calculated according to a previously described procedure (19). Briefly, fold changes were calculated across conditions by fitting a linear model to the data, and the statistical significance was estimated by a two-step process.…”
Section: Methodsmentioning
confidence: 99%
“…Immunomodulators were selected based on the fold change as well as adjusted P values for multiple comparisons. Immunomodulators with a fold change of at least 2 and a P value of Ͻ0.01 were considered significant (19).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The popularity of the MBA is the result of 1) the relative ease of covalently coupling of an analyte-capture ligand to spectrally classified carboxylated microspheres; 2) the simultaneous collection of multiple data points from a single specimen, eliminating the one-data point per well enzyme-linked immunosorbent assay (ELISA); 3) the direct proportionality of the fluorescence intensity of the reporter fluorochrome to the amount of captured analyte; and 4) the use of a 96-well format with up to 100 differently classified beads per well, which yield a potential of 9,600 data points per plate. These attractive features of the MBA conserve specimens and save on labor, time, and cost when compared with the ELISA format.…”
Section: Introductionmentioning
confidence: 99%